Development of E-LKPD Based on Search, Solve, Create, and Share (SSCS) to Empower Critical Thinking Skills in Class X High School Students' Biology Learning - Yulianti, Winda; Ndzani Latifatur Rofi'ah; Eka Vasia Anggis (Bioeduca : Journal of Biology Education, 2025)
The 21st century is characterized by rapid advancements in science and technology, making critical thinking an essential competency for students. Preliminary research at SMA Negeri 1 Limbangan revealed that 69.44% of students were in the very low category of critical thinking, with an average score of only 20%. This issue is attributed to teacher-centered learning and conventional instructional materials that provide minimal opportunities for analytical activities. This study aims to develop an Electronic Student Worksheet (E-LKPD) based on the Search, Solve, Create, and Share (SSCS) model for biology learning, evaluate the validity of the product, and analyze students’ responses. A Research and Development (R&D) approach using the 4-D model (Define, Design, Develop, Disseminate) was employed, focusing on the Develop stage, involving 36 Grade X students. Expert validation, including material, media, instructional methodology, critical thinking, and biology teachers, showed high validity (average >90%). A small-scale trial revealed positive student responses with an average score of 90.4%, indicating high readability and practicality. The findings demonstrate that the SSCS-based E-LKPD effectively enhances students’ critical thinking, facilitates inquiry-based learning, and bridges the gap between conventional learning materials and 21st-century competency needs. This study underscores the necessity of innovative digital instructional tools that integrate critical thinking models to prepare students for global challenges.